2017
DOI: 10.1002/jctb.5316
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ciprofloxacin, carbamazepine and ibuprofen on a membrane bioreactor system: Kinetic study and biodegradation capacity

Abstract: BACKGROUND: This study analyzed the effects of carbamazepine, ciprofloxacin and ibuprofen on the behavior of a membrane bioreactor (MBR) system treating urban wastewater that was doped continuously with three different concentrations of this mix of pharmaceuticals under a hydraulic retention time of 6 h. RESULTS: The degradation capacity of these chemicals and the heterotrophic kinetics regarding the organic matter removal were evaluated in the control and doping cycles.CONCLUSIONS: Although the MLSS decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Li and Zhang reported that no biodegradation of ciprofloxacin occurred during wastewater treatment with a conventional activated sludge process. Calero‐Díaz et al demonstrated that using a membrane bioreactor in aerobic conditions presented a high removal rate of ≤89% of ciprofloxacin, at HRT = 6 h. Ciprofloxacin was removed totally using a laboratory‐scale MBR compared with an anaerobic‐anoxic‐aerobic process . This indicated that MBR technology reduced the pharmaceuticals without reducing the removal capacity of the organic matter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Li and Zhang reported that no biodegradation of ciprofloxacin occurred during wastewater treatment with a conventional activated sludge process. Calero‐Díaz et al demonstrated that using a membrane bioreactor in aerobic conditions presented a high removal rate of ≤89% of ciprofloxacin, at HRT = 6 h. Ciprofloxacin was removed totally using a laboratory‐scale MBR compared with an anaerobic‐anoxic‐aerobic process . This indicated that MBR technology reduced the pharmaceuticals without reducing the removal capacity of the organic matter.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained metformin and ciprofloxacin removal were in the range of 70–77%. Removals of metformin and ciprofloxacin between 20% and 99% have been reported applying membrane bioreactor technology (MBR) under anaerobic, anoxic and aerobic conditions . A metformin removal of between 90% and 99.7% has been obtained through oxidation ditches .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a non-steady compound balance allowed for the prediction of the evolution of the pharmaceutical in the bioreactor. From this balance, the time required to ensure the working concentration of pharmaceutical was assessed according to Calero-Díaz et al [12]. To simulate punctual exposures to these pharmaceuticals, once the concentration of pharmaceutical was achieved, the pilot plant was run for 3 days under each doping.…”
Section: Operation Conditionsmentioning
confidence: 99%
“…The concentrations of carbamazepine, ciprofloxacin, and ibuprofen were 100, 10, and 100 µg/L, 1000, 100, and 1000 µg/L, and 5000, 500, and 5000 µg/L in the doping cycles 1, 2, and 3, respectively. The lowest mixing ratio between the different chemicals was based on the average values found in previous studies [12]; once the initial values were chosen, increasing concentrations were used to check the bioreactor by keeping the initial ratio constant. Moreover, this work was also designed to analyze the capacity of the bioreactor to adapt when different concentrations of pharmaceutical mixes were introduced into the biological process.…”
Section: Introductionmentioning
confidence: 99%